2016
DOI: 10.1007/s12600-016-0518-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification and evaluation of cultivable gut bacteria associated with peach fruit fly, Bactrocera zonata (Diptera: Tephritidae)

Abstract: The aim of the present study was to identify the cultivable gut bacteria associated with peach fruit fly, Bactrocera zonata, and evaluate their potential to attract adults of B. zonata. Based on culture-dependent characterization methods and 16S rRNA gene sequence analysis, bacteria were identified as members of family Enterobacteriaceae (BZM1, Klebsiella oxytoca), Microbacteriacea (BZM2, Microbacterium spp.) and Nocardiaceae (BZM4, Rhodococcus spp.). Molecular phylogeny placed Klebsiella oxytoca within gram n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 58 publications
4
29
0
Order By: Relevance
“…Owing to the experimental method employed in the studies by Naaz et al . () and Hamby et al . (), the full complement of microorganisms in the gut flora community was not fully explored, as the studies were restricted to those species that could be cultivated under laboratory conditions.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Owing to the experimental method employed in the studies by Naaz et al . () and Hamby et al . (), the full complement of microorganisms in the gut flora community was not fully explored, as the studies were restricted to those species that could be cultivated under laboratory conditions.…”
Section: Discussionmentioning
confidence: 86%
“…The microbial genera we identified include some of those found previously in other studies investigating the gut flora of fruit fly species. Fruit fly control strategies using metabolites, produced by bacteria or yeasts found in association with gut contents, have been developed for the peach fruit fly, Bactrocera zona (Naaz et al ., ). The results from our study have provided a list of candidate genera that, with further investigation, could enable a similar approach to be undertaken for use in future bait development to attract winter‐form D. suzukii .…”
Section: Discussionmentioning
confidence: 97%
“…Among those three symbiots, they found that metabolites produced by K. oxytoca had the highest attraction to the B. zonata adult females in a field bioassay. 16 Augustinos et al also isolated Enterobacter sp. from the Mediterranean fruit fly.…”
Section: Introductionmentioning
confidence: 99%
“…oxytoca had the highest attraction to the B . zonata adult females in a field bioassay . Augustinos et al .…”
Section: Introductionmentioning
confidence: 99%
“…The onion maggot causes large loses in onion yields and in other Liliaceae crops . These pests harbor a myriad of microbes, especially bacterial symbionts, in their guts, on their cuticle surface and in their habitat . Increasing numbers of reports have revealed the contribution of these microbial symbionts to improving insect host fitness, including supplementing food nutrition, overcoming host defenses, promoting larval development, facilitating kin recognition and mediating adult behavior .…”
Section: Introductionmentioning
confidence: 99%